Biological, chemical, and biochemical strategies for modifying glycopeptide antibiotics - Marschall, Edward (J Biol Chem, 2019)
Since the discovery of vancomycin in the 1950s, the glycopeptide antibiotics (GPAs) have been of great interest to the scientific community. These nonribosomally biosynthesized peptides are highly cross-linked, often glycosylated, and inhibit bacterial cell wall assembly by interfering with peptidoglycan synthesis. Interest in glycopeptide antibiotics covers many scientific disciplines, due to their challenging total syntheses, complex biosynthesis pathways, mechanism of action, and high potency. After intense efforts, early enthusiasm has given way to a recognition of the challenges in chemically synthesizing GPAs and of the effort needed to study and modify GPA-producing strains to prepare new GPAs to address the increasing threat of microbial antibiotic resistance. Although the preparation of GPAs, either by modifying the pendant groups such as saccharides or by functionalizing the N- or C-terminal moieties, is readily achievable, the peptide core of these molecules—the GPA aglycone—remains highly challenging to modify. This review aims to present a summary of the results of GPA modification obtained with the three major approaches developed to date: in vivo strain manipulation, total chemical synthesis, and chemoenzymatic synthesis methods.